Educational intervention and livestock ownership successfully improved the intake of animal source foods in 6-23 months old children in rural communities of Northern Ethiopia: Quasi-experimental study. - Mekonnen Haileselassie; Getachew Redae; Gebretsadik Berhe; Carol J Henry; Michael T Nickerson; Afework Mulugeta (PLoS ONE, 2022)
Background Animal source foods (ASFs) are rich in high-quality proteins, including essential amino acids and highly bioavailable micronutrients vital for child growth and cognitive development. But, the daily consumption of ASFs among 6-23 months old children is very low in Tigray, Northern Ethiopia. Objective The study aimed to assess the effectiveness of nutrition education intervention to improve the consumption of ASFs among 6-23 months old children from rural communities with strict religious fasting traditions of avoiding intake of ASFs in Northern Ethiopia. Methods A quasi-experimental study was conducted in two food insecure districts namely Samre Seharti (intervention) and Tanqua Abergele (comparison). The mother-child pairs in the intervention group (n = 140) received nutrition education based on the barriers and available resources for optimal consumption of ASFs among children and followed up for nine months. The mother-child pairs in the comparison group (n = 153) received routine nutrition education. The data were collected using a pre-tested structured questionnaire. The baseline and endline data assessment included interviews on socio-demographic and socio-economic status, dietary intake, and child feeding practices. The effectiveness of the intervention was measured using the difference-in-difference (DID) analysis model. Results At endline, the consumption of ASFs among children was 19.5 percentage points higher in the intervention group compared with the comparison group (p = 0.008). In addition, there was a significant increase in egg consumption among children in the intervention group (DID of 16.9, p = 0.012) from the comparison group. No child was consuming meat at baseline in both the intervention and comparison arms and it was very low at endline (5.2% vs. 7.9%). Overall, the proportion of children that consumed eggs in the intervention group was higher than in the comparison group in households that owned sheep and goats (4.8% vs. 21.4%, p = 0.050) and chicken (6.3% vs. 43.8%, p = 0.002) after education interventions. However, no statistically significant difference was observed between cow ownership and milk consumption among children (p>0.05). Conclusions Age-appropriate educational interventions for mothers and owning small livestock in the household can improve the consumption of ASFs and eventually the minimum diet diversity of children in communities with strict religious traditions of avoiding ASFs during the fasting seasons.